Taxation of Capital Gains : A Review of the Main Issues - Andersson, Krister (IMF Working Papers; Working Paper, 1991)
This paper reviews the main issues that needs to be addressed in the taxation of capital gains. The main focus of the paper is on the tax treatment of capital gains in the United States. The impact of inflation on asset values and the taxation of gains have led to calls for an inflation-adjusted taxation of capital gains. Others have called for the exclusion of a part of the nominal gains from taxation. This paper argues that if the exclusion method is used, the exclusion rate should increase as the holding period gets longer.